Desain Kinerja Pegawai Keuangan - Setiawan, Yana; Supriatna, Nono (Universitas Pendidikan Indonesia, 2021)
AbstractThe problem in this study is related to the low performance of financial employees which is described by the low absorption power so that it has an impact on performance achievements and organizational sustainability. The purpose of this study is to describe and analyze the performance design of financial employees that analyzes accounting information systems on financial performance. The results of the research are (1) the accounting information system is included in the effective category with the user satisfaction factor which gives the most dominant contribution; (2) the financial Staff Performance is in the high category with the task performance factor giving the most dominant contribution; (3) The accounting information system has a positive and significant effect on the performance of financial employees